Preparation and Characterization of Biodegradable Hydrogels Based on Ulvan, a Polysaccharide from Green Seaweeds. Issue 2 (May 2016) - Yoshimura, Toshio; Hirao, Nana; Fujioka, Rumiko
Preparation of superabsorbent hydrogels based on ulvan, a polysaccharide extracted from green seaweed Ulva, was investigated by crosslinking ulvan with divinylsulfone (DVS) under alkaline aqueous condition. Extraction of ulvan from Ulva was performed at room temperature or at 80°C. Gelation was observed constantly when ulvan obtained at 80°C was crosslinked with DVS, but not always when that obtained at room temperature was used. The optimal preparation condition of hydrogels was investigated by changing the feed amount of DVS. Among those examined, the highest water absorbency was obtained with the sample for DVS feed ratio of 20 wt%. Maximum absorbency in pure water was 80 g/g, which was considerably lower than that of crosslinked sodium polyacrylate, commercially available (300 g/g). Biodegradation speed of the hydrogels in the present study depended on the feed amount of DVS.